Construction of Partially Linear Model of Distribution Coronevirus in Ukraine and the World (Моделювання, керування та інформаційні технології, 2020)
The author proposes a piecewise linear model of the spread of coronavirus 2019 based on the analysis of statistical studies obtained by the World Health Organization (WHO), the Ministry of Health (MH) of Ukraine and the Center for Mathematical Modeling of the NAS of Ukraine within seven months from appearance of the virus. Based on this model and forecasting the rations of growth of the epidemiological disease at COVID-2019, made estimates of the time of disappearance of virus outbreak and a continuous decrease in the number of diseases of persons in need of hospitalization.              The obtained results have both theoretical and applied significance, as they allow, at least, to plan and lead an active lifestyle, save material and human resources, effectively and adequately respond to the manifestations of viral diseases until their complete disappearance.